Niger: A famine foretold - Michael Fleshman (Africa Renewal, 2005)
The seasonal rains returned to southern Niger in June, coaxing the green millet stalks from the dry earth and signalling an end, hopefully, to a food shortage that has left some 2.4 million Nigeriens — including 800,000 children — vulnerable to malnutrition. International relief workers have also started to arrive to distribute the emergency rations needed until the harvest is in.